An Investigation of Cognitive and Affective Changes During Group Imagery Rescripting for Social Anxiety Disorder. Issue 5 (September 2022) - McCarthy, Aoibheann; Bank, Samantha R.; Campbell, Bruce N.C.; Summers, Mark; Burgess, Melissa; McEvoy, Peter
Highlights: Investigated cognitive and affective changes during group imagery rescripting (ImRs) Participants were a clinical sample with social anxiety disorder. ImRs was associated with large changes in strength and valence of core beliefs. Affective changes were largest between phases 1 and 2 of ImRs. Abstract: Recurrent, negative self-imagery is common in social anxiety disorder (SAD). Imagery rescripting (ImRs) is an effective therapeutic technique that aims to target past aversive memories to modify their associated meanings, and update the encapsulated negative schematic beliefs. The current study aimed to extend previous research by investigating the cognitive and affective shifts during each phase of ImRs delivered within a group cognitive behavioral therapy protocol. Participants ( N = 32) retrieved an aversive memory associated with social anxiety and were guided through brief cognitive restructuring, prior to completing ImRs. Core beliefs associated with the memory (strength and valence) and fear of negative evaluation were assessed before and after ImRs and affect was assessed following each phase. Strength and affective valence of encapsulated core beliefs about the self, others, the world, and the image itself significantly reduced following ImRs, and core beliefs were updated to become more positive. Participants reported large affective shifts early in the process, with smaller shifts in the later stages. Fear of negative evaluation did not significantly reduce following ImRs. Outcomes provide some support for cognitive and affective changes during group ImRs for SAD and suggest future research directions to investigate longer-term impacts and to better understand the underlying mechanisms of the technique.